The performance of workers through knowledge sharing and knowledge management: A quantitative analysis of SMEs - Sutrisno (Edelweiss Applied Science and Technology, 2024)
This research aims to conduct a comprehensive review of the relationship between knowledge sharing, knowledge management practices, and worker performance in the SME sector. This research employs two primary theories, knowledge sharing and knowledge management, along with individual performance constructs, to identify correlations that serve as key findings. Comprehensive results from research are beneficial for academics and can serve as long-term references. The study employed structural Equation Modeling (SEM) and Partial Least Squares (PLS) as its methodologies. It focused on 189 SMEs located in Semarang Regency, Indonesia. Non-random sampling, specifically purposive sampling, was utilized to select participants. Data were gathered through online questionnaire distribution to the chosen respondents. The findings indicate a robust and statistically significant positive correlation between knowledge sharing, knowledge management, and the performance of SME workers. Knowledge sharing and knowledge management ensure the availability and regularity of knowledge that supports day-to-day activities, while effective knowledge access and distribution increase employees' responsiveness to changing market and customer needs. This finding provides practical implications for SME owners and managers in developing strategies to enhance their organizational performance. By implementing effective knowledge sharing and management systems, SMEs can gain a competitive advantage, increase productivity, and enhance adaptability to market changes.